Succinylation profiles of brain injury after intracerebral hemorrhage - Yuan-Hong Deng (Public Library of Science (PLoS), 2021)
Protein posttranslational modifications (PTMs) regulate the biological processes of human diseases by genetic code expansion and cellular pathophysiology regulation; however, system-wide changes in PTM levels in the intracerebral hemorrhage (ICH) brain remain poorly understood. Succinylation refers to a major PTM during the regulation of multiple biological processes. In this study, according to the methods of quantitative succinyllysine proteomics based on high-resolution mass spectrometry, we investigated ICH-associated brain protein succinyllysine modifications and obtained 3,680 succinylated sites and quantified around 3,530 sites. Among them, 25 succinyllysine sites on 23 proteins were upregulated (hypersuccinylated), whereas 13 succinyllysine sites on 12 proteins were downregulated (hyposuccinylated) following ICH. The cell component enrichment analysis of these succinylproteins with significant changes showed that 58.3% of the hyposuccinylated proteins were observed in the mitochondria, while the hyper-succinylproteins located in mitochondria decreased in the percentage to about 35% in ICH brains with a concomitant increase in the percentage of cytoplasm to 30.4%. Further bioinformatic analysis showed that the succinylproteins were mostly mitochondria and synapse-related subcellular located and involved in many pathophysiological processes, like metabolism, synapse working, and ferroptosis. Moreover, the integrative analysis of our succinylproteomics data and previously published transcriptome data showed that the mRNAs matched by most differentially succinylated proteins were especially highly expressed in neurons, endothelial cells, and astrocytes. Our study uncovers some succinylation-affected processes and pathways in response to ICH brains and gives us novel insights into understanding pathophysiological processes of brain injury caused by ICH.